2023
DOI: 10.1021/acsami.2c22179
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Engineering of Lead Acetate-Based Precursors for High-Open-Circuit Voltage Wide-Bandgap Perovskite Solar Cells

Abstract: Wide-bandgap (WBG) perovskites have great potential for inclusion in efficient tandem solar cells, but large open-circuit voltage losses have limited device performance to date. Here, we show that a high-quality WBG perovskite, FA0.83Cs0.17Pb­(I0.8Br0.2)3, with enlarged grain sizes and improved crystallinity can be achieved by incorporating lead chloride (PbCl2) into a lead acetate (PbAc2)-based precursor. The improved film quality resulted in the suppression of nonradiative recombination and a reduction in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Both phase segregation and defects can contribute to instability in WBG perovskites. 43 On the one hand, the migration of halide anions, facilitated by structural defects within the perovskite lattice, exerts a significant influence on phase segregation. Investigations have indicated that phase segregation predominantly manifests at grain boundaries, known for their heightened defect density compared to the grain interior.…”
Section: Introductionmentioning
confidence: 99%
“…Both phase segregation and defects can contribute to instability in WBG perovskites. 43 On the one hand, the migration of halide anions, facilitated by structural defects within the perovskite lattice, exerts a significant influence on phase segregation. Investigations have indicated that phase segregation predominantly manifests at grain boundaries, known for their heightened defect density compared to the grain interior.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S4 presents the time evolution of PL spectra of a perovskite film in a nitrogen environment. The segregation of iodide ions stopped after 45 min of light exposure, implying saturation of iodide ions at the grain boundaries . The PL spectra of the target sample remain nearly unchanged, even after extended illumination.…”
mentioning
confidence: 99%
“…Various lead halide (PbCl 2 ) and nonhalide lead precursors including Pb­(OAc) 2 (OAc = CH 3 CH 2 COO – ), Pb­(NO 3 ) 2 , Pb­(acac) 2 (acac = (CH 3 COCHCOCH 3 ) − ), and PbCO 3 have been explored as potential precursors for perovskite solar cell preparation using conventional organic solvent methods. However, the performance of the resulting PSCs has been hindered by challenges related to inadequate phase and morphological control. …”
mentioning
confidence: 99%